Perubahan Makna Pasal 6A Ayat (2) UUD 1945 - Ziffany Firdinal (The Constitutional Court of the Republic of Indonesia, 2016)
This article examines the changes in the meaning of Article 6A paragraph (2) of the Indonesian 1945 Constitution, related to the requirements for nominating Presidential and Vice Presidential candidates by a political party or an alliance of parties contesting in the parliamentary election prior to the Presidential election. Further provisions termed more precisely in Article 9 of Law No. 42 of 2008 on Presidential and Vice Presidential Election; some additional requirement that political parties or alliance of parties gain valid votes of at least 20% of total votes nationally or a minimum 25% of seats in the House of Representatives, which is conceptually known as ‘presidential threshold’. Based on the Constitutional Court Verdict No. 51-52-59/PUU-VI/2008, provisions on the candidacy at the Act level were declared constitutional with some terms, that there are some dissenting opinions among judges who adjudicated the constitutional norms during the judicial review of the Act. Examination results obtained is that there have been change in meaning, in this case, the change takes a form of narrowing of meaning of the normative provisions of Article 6A paragraph (2) in a consequence to the provisions set in Article 9 of Law No. 42 of 2008. In order to provide legal certainty associated to the narrowing of this provision’s meaning, an ammendment is required to Article 6A paragraph (2) to reinforce the measures in the Presidential and Vice Presidential candidate nomination, in this case whether it is in line with the Constitutional Court verdict on judicial review of Article 9 of Law No. 42 of 2008 on Election of President and Vice-President or not.